2007
DOI: 10.1108/09556220710725739
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of personal and delay allowances using work sampling technique in the sewing room of a clothing manufacturer

Abstract: PurposeThe aim of this paper is to study the operator activities in garment industry and the percentages of distribution of operations and to analyze the personal and delay allowances by observing the operations and deriving the ratios within a manufacturing period.Design/methodology/approachA work sampling technique is used. Relevant reports (1978‐2004) are studied to give the basis and methodology of the technique. In accordiance with work sampling techique, the operations to be observed in a sewing room are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…One possible reason for the lack of investigations could be due to the high complexity of the industry. According to [14], the garment manufacturing industry is more complicated than many other industries as it consists of various machines, labors and thousands of bundles of cutting pieces producing different styles simultaneously. Conventionally, in the garment industry, there is a lack of standardized approaches in resources management where human judgments are used to determine resources planning decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One possible reason for the lack of investigations could be due to the high complexity of the industry. According to [14], the garment manufacturing industry is more complicated than many other industries as it consists of various machines, labors and thousands of bundles of cutting pieces producing different styles simultaneously. Conventionally, in the garment industry, there is a lack of standardized approaches in resources management where human judgments are used to determine resources planning decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is performed in those activities that do not have a work method and very consuming time activities and could be more than one monitored resource. This technique has been used to measure productivity in the construction area [2], automotive industry [3], brewing manufacture [5], and clothing industry [6], but it can actually be used to measure the efficiency of any company.…”
Section: Introductionmentioning
confidence: 99%
“…Personal and delay allowances are very important for every industry [6]. Having an incorrect standard time directly affects productivity, operators, and quality, among other metrics in the company.…”
Section: Introductionmentioning
confidence: 99%
“…They are allowed to take up to 15% time for relaxation and machine attention as allowances [8] .But beyond the allowances, the sewers wasted their time in involvement with some non-value added activities such as gossiping to the other workers, reworking, waiting for work, being idle intentionally. In sewing section it is found that garment workers spent 72.7% time in productive activities and the 23.2%time in personal allowances and unavoidable delay [9]. Another study revealed that the sewing operators engaged in 40% time in main operation 33.25% time in associated operation and rest of 26.7% in allowances [10].…”
Section: Introductionmentioning
confidence: 99%
“…The work sampling studies [9] & [10] are conducted in the sewing floor to identify delay and other allowances to but not to measure SMV of the sewing process. Work sampling study result will help the management to visualize the sewing floor and to take right initiative to minimize the wastage through proper supervision and line balancing.…”
Section: Introductionmentioning
confidence: 99%